Edukasi Penyuluhan Menjaga Dokumen Berharga dan Barang Pribadi bagi Siswa UPT SD Negeri 69 Gresik (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2026)
This Community Service Program (Kuliah Kerja Nyata/KKN) aimed to provide education on the importance of maintaining important documents and personal belongings for students at UPT SD Negeri 69 Gresik. The main issue underlying this activity was the low level of students’ understanding regarding the types of important documents and proper ways to store personal belongings safely and neatly. The activity was conducted using an interactive and educational approach, including simple material delivery, light discussions, and the use of a document storage teaching aid as a learning medium. The program was implemented on January 31, 2026, involving elementary school students as the main participants. The results showed that students responded positively and enthusiastically to the activity and demonstrated an improved understanding of the importance of maintaining important documents and personal belongings from an early age. This program is expected to foster positive habits and a sense of responsibility among students toward their personal belongings both at school and at home.